Mechanism of root hair deficiency and growth-promoting effect of endophytic mycorrhizal fungi in blueberry - YOU Shibei; XU Jiahui; GUO Yiwen; LIAO Fanglei; YANG Li; CHEN Wenrong; GUO Weidong (浙江大学学报. 农业与生命科学版, 2020)
In order to elucidate the mechanism of root hair deficiency in blueberry, six key genes involved in root hair development were isolated and identified using ‘Brigitta’ blueberry seedlings as materials; meanwhile, to screen probiotic endophytic mycorrhizal fungi and study their mechanism of promoting seedling growth, 12 strains of endophytic mycorrhizal fungi were isolated and purified from the roots of mature blueberry bushes of ‘Sharpblue’ and ‘O’Neal’. Then these isolated fungi were separately inoculated on ‘Gulfcoast’ blueberry seedlings. The results showed that the negative regulators in root hair development, GL2, WER and TTG were expressed in root hairs, while the positive regulators TRY, CPC and ETC1 were not expressed, which may be the main mechanism resulted in root hair deficiency in blueberry. The isolated mycorrhizal fungi mainly belonged to the genera of Fusarium, Talaromyces, Gibberella, Penicillium and Aspergillus. Inoculation experiments showed the strains A1, A4, X2 and X22 significantly promoted the growth of blueberry; meanwhile, A1, A4 and X22 significantly increased root activity; A4, X2 and X22 significantly acidified the rhizospheric soil. In the A4 and X22 treatment groups, the total phosphorus contents of leaves increased significantly, but no obvious decrease was observed in the available phosphorus content in rhizosphere. Therefore, it can be inferred that the mycorrhiza formed by the strains of A4 and X22 can enhance the phosphorus availability. Vitamin B2, related to plant growth and resistance, was detected in the secretion of X22, which suggests that biosynthesis of vitamin B2 may be another plant growth-promoting mechanism of ericoid mycorrhizae.